Taller Gráficomusical para fortalecer la autorregulación de emociones de niños de 3 años del centro educativo privado. Trujillo, 2018 - Laguna García, Jennifer Maricruz Natalie (2019)
This research entitled: Graphic music workshop to strengthen the self-regulation of emotions of 3 year olds children from the private educational center, Trujillo, 2018; its principal purpose is to strengthen emotional self-regulation in children, in an interpersonal and intrapersonal way. The research was an applied quasi experimental type, having a control group in which the pretest and post-test was applied and an experimental group where a pre-test was applied, then the proposed graphic music workshop and finally applied the post-test, giving as efficient results. The exhibition consisted of 20 children, using the yellow classroom of 3 years "A" of the private school "Rafael Narváez Cadenillas" like the principal place of our research. The results obtained from the pre-test show that children had a low level in their emotional self-regulation. After the application of the investigation the results show a significant increase in this topic. All this shows that the application of the graphic music workshop helped to strengthen the self-regulation of emotions significantly in 3 year olds children, thus obtaining in the experimental group a score of 17.9 points in the dimension with itself and 19.5 points dimension with others